Les affiches de la lutte contre le sida - Alexandre Klein; Gabriel Girard (Glad!)
The HIV-AIDS epidemic has led to the production of a multitude of documents, whether by the authorities responsible for its management, by patients and their relatives or by the activist and community associations that supported them. Among these productions, the posters occupy a special place as they characterized – one thinks only of the famous Silence = Death of the eponymous collective which alone embodies the epidemic and its political issues – both the prevention strategy against HIV and related socio-political mobilizations. These full-fledged archives thus offer a unique perspective on the course of the epidemic, but also on the involvement of different actors – governmental, community, or associative – in the fight against the virus. This is what we intend to demonstrate in our project on the history of HIV/AIDS in Montreal as seen through posters of the fight against this epidemic.